A Pacchionian Puzzle. (March 2020) - Nazir Khan, M.; Shaw, Brett H.; Wallace, Carla J.; Metz, Luanne
Abstract : A 73-year-old male with a history of chronic ataxia presented with transient facial droop to the Emergency Department. A CT angiogram and MRI with diffusion weighted imaging (DWI) were negative for stroke. However, incidental note was made of numerous giant arachnoid granulation pits in the posterior fossa predominantly involving the left occipital bone (Figure 1 ). These arachnoid pits demonstrated multiple foci of herniation of the adjacent cerebellar parenchyma into the pits with gliosis of the herniated parenchyma and focal encephalomalacia of the subjacent cerebellar parenchyma. Review of bone windows on a remote CT brain performed almost 13 years earlier confirmed this to be a longstanding abnormality (Figure 2 ). The patient's physical exam was suggestive of cerebellar ataxia with left-sided dysmetria on finger to nose testing and a wide-based unsteady gait.